Konsepsi Taklid Mazhab Syiah Imamiyah - Muhammad Zuhdi Zaini (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
For a long time, the term “taqlid” has carried a negative connotation, especially when accompanied by the word “blind”. However, in the religious thought tradition of Shia Islam, the term